Experimental Setup of Smart Traffic Control using Wireless Sensor Networks - Abdelsamee, Nagwan M.; Alsulaimani, Hanoof; Albatati, Nouf (2018 21st Saudi Computer Society National Computer Conference (NCC), 2018)
Traffic jam is one of the major concerns to be considered nowadays. Basically, Vehicular traffic intersects at the junctions of the road and is controlled by the traffic signals. Traffic signs need a good coordination and control to ensure the smooth and safe flow of the vehicular traffic which can minimize the possibilities of traffic jams, caused by long delays of the traffic lights. The main objective of this study is to design a smart traffic monitoring system using wireless sensor network (WSN). WSN is an emerging wireless networking technology that support large scale monitoring of physical system. In this paper we propose a low cost solution for smart traffic monitoring using WSN. The proposed system is a demonstration of four junctions with Four unidirectional lanes. Each Lane is equipped with an ultrasonic wireless sensor node that is responsible for monitoring the traffic load in that lane. The recorded traffic loads from all lanes are further processed via a base station that is responsible for opening the traffic sign for Heavy loaded traffic lane. The hardware implementation of our proposed WSN has been done using Arduino microcontrollers and ZigBee transceivers. The wireless communication is based on IEEE 802.15.4 due its ultra-low power consumption. Compared to the current traditional traffic monitoring paradigms, the proposed system has more lower cost, easy-to-deploy, easy to maintain, and higher coverage area.